2017
DOI: 10.5535/arm.2017.41.3.475
|View full text |Cite
|
Sign up to set email alerts
|

Research Designs and Statistical Methods Trends in the Annals of Rehabilitation Medicine

Abstract: ObjectiveTo investigate trends of the research designs and statistical methods in the Annals of Rehabilitation Medicine (ARM) published from 2005 to 2015 through a comparison of articles with the Archives of Physical Medicine and Rehabilitation (APMR).MethodsThe authors reviewed all articles published in ARM and APMR for the years 2005 and 2015 in order to determine their research designs as well as their statistical methods used in each article.ResultsIn ARM, randomized controlled trials increased from 4.5% i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…He found a considerable increase in the use of statistics and reported that a much greater use of complex statistical methodology in medical research was detected. The review articles regarding the use of statistics in medical journals [ 6 - 9 ] reflect Altman’s findings. Altman [ 10 ] also said as a final comment, “Reviewing medical papers is difficult, time-consuming, occasionally frustrating, and educational.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…He found a considerable increase in the use of statistics and reported that a much greater use of complex statistical methodology in medical research was detected. The review articles regarding the use of statistics in medical journals [ 6 - 9 ] reflect Altman’s findings. Altman [ 10 ] also said as a final comment, “Reviewing medical papers is difficult, time-consuming, occasionally frustrating, and educational.…”
Section: Discussionmentioning
confidence: 90%
“…Freshwater 5 published a letter pleading for improvements in statistical analyses in plastic surgery. Some medical journals have published articles like this one, providing a systematic review and/or analysis of trends in the statistical methods applied 6 7 8 9 . However, we did not find such articles in the field of plastic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Rehabilitation medicine [18] is a medical application subject with independent theoretical basis and functional evaluation method, with large application scale and high treatment technology. Its purpose is to speed up the rehabilitation process of human injury, prevent and reduce the degree of disability, and help the disabled return to society.…”
Section: Exercise Rehabilitation Trainingmentioning
confidence: 99%
“…In this regard, review articles have recently been published focusing on the statistical methods used in the original articles of scientific journals. [11][12][13][14][15][16] Due to the importance of the content mentioned in the previous paragraphs, the present study aimed to identify and review statistical methods, sample size, study design, statistical population, and type of software used in the original articles and investigate their relationship with the acceptance period (interval between the received and accepted dates mentioned in the articles) of articles published in the Archives of Iranian Medicine in the period 2015 to 2019. Statistical review of journal articles is usually done over a period of 5 or 10 years.…”
Section: Introductionmentioning
confidence: 99%